PETA KEKERASAN DALAM RUMAH TANGGA (Studi Atas Perkara Perceraian di Pengadilan Agama Batang Tahun 2015) - Widyastuti, Widyastuti (IAIN Pekalongan, 2016)
This paper is the result of research that maps of domestic violence in divorce cases in Batang Religious Court by 2015. This literature research used a qualitative approach. Secondary data sources such as the archives of the Religious Court divorce case Batang 2015 and; other data that support the research. Data collection techniques using documentation and interviews. Analysis techniques using interactive analysis model. The results showed that, the map of domestic violence in divorce cases in Batang Religious Court in 2015, among others: physical violence, which in divorce case referred to, physical cruelty and mental cruelty, as many as 32 cases; psychological violence, as many as 628 cases; sexual violence, no and; economic violence (penelantara households), as many as 1036 cases.Paper ini merupakan hasil penelitian yang memetakan KDRT dalam perkara perceraian di Pengadilan Agama Batang pada tahun 2015. Penelitian kepustakaan (Library Research) ini menggunakan pendekatan kualitatif. Sumber data sekunder berupa arsip perkara perceraian dari Pengadilan Agama Batang tahun 2015 dan; data lain yang mendukung penelitian. Teknik pengumpulan data menggunakan dokumentasi dan wawancara. Teknik analisis menggunakan model analisa interaktif. Hasil penelitian menunjukan bahwa, peta Kekerasan dalam Rumah Tangga pada perkara perceraian di Pengadilan Agama Batang tahun 2015, meliputi: kekerasan fisik, yang dalam perkara perceraian disebut dengan, kekejaman jasmani dan kekejaman mental, sebanyak 32 perkara; kekerasan psikis, sebanyak 628 perkara; kekerasan seksual, tidak ada dan; kekerasan ekonomi (penelantara rumah tangga), sebanyak 1036 perkara.